2021
DOI: 10.1016/j.neurobiolaging.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma Aβ40/Aβ42 ratio and brain Aβ accumulation: testing a whole-brain PLS-VIP approach in individuals at risk of Alzheimer's disease

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
(122 reference statements)
0
3
0
1
Order By: Relevance
“…Moreover, genetic screening revealed that mutations in KCNJ10 play a significant role in neurodegenerative disorders such as AD [ 53 ]. VIP may significantly boost microglial uptake of fibrillar Aβ42 and this heightened phagocytic function relied on the activation of the Protein kinase C signaling pathway in AD pathology [ 97 ]; VIP was also reported to be involved in Aβ accumulation in AD [ 98 ]. A study pointed out an Interaction between Aβ and SST [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genetic screening revealed that mutations in KCNJ10 play a significant role in neurodegenerative disorders such as AD [ 53 ]. VIP may significantly boost microglial uptake of fibrillar Aβ42 and this heightened phagocytic function relied on the activation of the Protein kinase C signaling pathway in AD pathology [ 97 ]; VIP was also reported to be involved in Aβ accumulation in AD [ 98 ]. A study pointed out an Interaction between Aβ and SST [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include familial genetics and family history, ethnicity, inter-current illness, multiple parameters associated with gender and aging, the environment, diet and lifestyle and other factors associated with the intrinsic complexity of the disease itself, neurodiagnostic variation in neuroimaging, and neuropathologically via the pre-clinical, clinical and Braak staging of the disease, multiple interactive parameters including CSF and plasma Aβ40/ Aβ42 ratios and the anatomical location of Aβ accumulation (Dong et al, 2017;DeTure and Dickson, 2019;Habes et al, 2020;Jellinger et al, 2022). Other parameters of AD diversity and heterogeneity include the abundance, speciation and inflammatory potential of different senile plaque (SP) and neurofibrillary tangle (NFT) isoforms and densities in anatomical regions of the brain implicated in behavior, cognition and memory (Dong et al, 2017;DeTure and Dickson, 2019;Habes et al, 2020;Lemercier et al, 2021;Bellenguez et al, 2022;Jellinger 2022). This significant heterogeneity in the presentation of AD, currently referred to as "the AD spectrum or continuum", requires both a highly individualized diagnostic approach and treatment strategy.…”
Section: Mirna Abundance Complexity and Speciation In Admentioning
confidence: 99%
“…Currently the "precision medicine" approach has been to investigate early pathophysiological changes of AD to fully capture the complexity of the disease, and has been essential to develop timely screening, detection, diagnostic, prognostic and therapeutic interventions in significantly heterogeneous AD patient populations. Importantly "precision medicine" delineates which therapeutic approach or treatment strategy would be the most effective for a specific individual, at a specified disease stage, across multiple medical research fields that include molecular-genetics, imaging technologies, neuroscience, neurology and psychiatry and the identification of miRNA-and/or mRNA-based biomarkers in the CSF and blood (Hampel et al, 2019;Lemercier et al, 2021;Giampietri et al, 2022;Jellinger 2022;Yamamoto et al, 2022). "Precision medicine" achieves the greatest success when multiple interdisciplinary diagnostic parameters are integrated to yield the most accurate diagnostic analysis of the AD patient who can be subsequently treated using an individualized combination therapy approach or multi-target-directed methodologies.…”
Section: Mirna Abundance Complexity and Speciation In Admentioning
confidence: 99%
“…Hingegen war der Biomarker p-tau217 in der Lage, die Tauablagerungen im Tau-PET über einen längeren Zeitraum, die entstehende Hirnatrophie und die geistige Leistungsunfähigkeit zu prognostizieren. Diese Ergebnisse konnten für die Ratio von Aß42/Aß40 im Plasma durch eine Studie von 30 in einer Kohorte von Patienten mit Gedächtnisbeeinträchtigung (n=261) bestätigt und erweitert untersucht werden, da die Aß42/Aß40 Ratio im Blutplasma assoziiert war mit einer erhöhten Anreicherung von Aß im PET besonders in den Regionen, die präklinisch bei der Alzheimer-Krankheit betroffen sind wie das Ruhezustandsnetzwerk (Default Mode Network), aber auch in zuvor mit der Alzheimer-Krankheit nicht assoziierten Netzwerken wie das Exekutiv- und Salienz-Netzwerk.…”
Section: Biomarker Kandidaten Im Blutunclassified